2020
DOI: 10.1021/acsanm.0c01324
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorods as Photoacoustic Nanoprobes to Detect Proinflammatory Macrophages and Inflammation

Abstract: Key hallmarks of inflammation include proinflammatory (M1) macrophages and production of reactive oxygen species (ROS). Therefore, we developed a ROS-sensitive, photoacoustic (PA) nanoprobe capable of identifying M1 macrophages in vitro. The nanoprobe is a silica-coated gold nanorod (AuNR), which provides a stable PA signal, combined with an adsorbed polyelectrolyte-dye (poly-d-lysine (PDL)-IR775c) coating that exhibits ROS sensitivity. By monitoring the ratio between these two PA intensities, we can determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…While the stability of this electrostatically constructed particle may be a concern for ultimate application in vivo , our particle provides an attractive nanoparticle-based platform for ultimate use as a real-time, phenotypic indicator of macrophages for use in ACTs, and we are working on a next-generation thiolated version to improve stability. Future studies will aim to incorporate NIR dyes for in vivo imaging, 37 or translate this system to non-invasive trackable platforms, such as photoacoustic imaging, 38 for a more clinic-ready approach.…”
Section: Discussionmentioning
confidence: 99%
“…While the stability of this electrostatically constructed particle may be a concern for ultimate application in vivo , our particle provides an attractive nanoparticle-based platform for ultimate use as a real-time, phenotypic indicator of macrophages for use in ACTs, and we are working on a next-generation thiolated version to improve stability. Future studies will aim to incorporate NIR dyes for in vivo imaging, 37 or translate this system to non-invasive trackable platforms, such as photoacoustic imaging, 38 for a more clinic-ready approach.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to endogenous contrast agents, an exogenous contrast agent offers better image quality and enhanced signal of contrast agents. Exogenous contrast agents can be divided into dyes-based materials such as indocyanine green, prussian blue, methylene blue, and nanoparticle-based contrast agents such as quantum dots, gold nanoparticles, upconversion nanoparticles, and copper sulfide nanoparticles . Inorganic materials exhibit good photothermal stability and higher photothermal convention efficiency.…”
Section: Contrast Agents For Pai In Small Animalsmentioning
confidence: 99%
“…12 Several studies have demonstrated the efficacy of combining AuNRs and drugs as a strategy against inflammation and cancer. 13,14 This is because, unlike other materials, gold is deemed minimally toxic, rendering it suitable for biological and medical applications. Moreover, gold absorbs near-infrared (NIR) lasers and efficiently converts the absorbed energy into heat.…”
Section: Introductionmentioning
confidence: 99%